Households willingness to join and pay for community-based health insurance: implications for designing community-based health insurance based on economic Status in Ethiopia - Zewdie Birhanu; Morankar Sudhakar; Mohammed Jemal; Desta Hiko; Shabu Abdulbari; Bikiltu Abdisa; Badassa Wolteji Chala; Getnet Mitike; Tigist Astale; Nimona Berhanu (PLoS ONE, 2025)
Background Despite the encouraging results achieved by community-based health insurance in Ethiopia, the program faces significant challenges. Among these challenges is the current practice where premium contributions to Community Based Health Insurance are either a flat rate or based solely on family size, rather than considering households’ socio-economic status The overall aim of this study was to assess households’ willingness to join and pay for Community Based Health Insurance in reference to socio-economic status to design sliding scale-based Community Based Health Insurance contributions in Ethiopia. Methods A community based cross-sectional study was conducted in districts from two different contexts: urban areas and agrarian areas in two major regions in Ethiopia, namely Oromia, and Amhara. A double-bounded dichotomous contingent valuation method was used to determine households’ willingness to pay. Descriptive statistics were used to summarize the data. A chi-square test was used to assess background factors associated with willingness to join and pay for Community Based Health Insurance, and tobit regression analyses were conducted to identify factors that determine the amount of willingness to pay for Community Based Health Insurance. The statistical significance of all results was interpreted using an adjusted two-sided Type I error rate of 0.05. Result A total of 786 households participated in this study. Overall, 532 (67.7%) study households have ever participated in the Community Based Health Insurance scheme. The reason for never participating was unaffordability of payment (30.3%), and they stated that the service was unsatisfactory (21.7%). Generally, 647 (82.3%) of the households were willing to join Community Based Health Insurance or renew their scheme membership in the future, with higher willingness among rural and urban residents and households with food insecurity (p < 0.05. The average amount households were willing to pay was 538.2 Ethiopian Birr with mode (570.0 Ethiopian Birr). In contrast with the existing premium contribution policy, the vast majority of households preferred premium contributions that considered households’ economic status (81.2%). Increased household size, better household food security, and being rural residents, increased satisfaction with the scheme; and rural households’ economic status significantly predicted the value of money households are willing to contribute to Community Based Health Insurance (p < 0.05). Conclusion This study revealed a strong willingness among community members to participate in or renew their membership in the Community Based Health Insurance scheme, with a clear preference for a socio-economic-based sliding scale approach over current flat rate or family size-dependent premium systems. This preference highlights the potential for transforming towards more equitable citizen contributions. Policymakers should therefore consider household economic status, alongside factors like household food security and family size, in determining Community Based Health Insurance membership fees. Furthermore, enhancing the quality of healthcare services is essential to boosting Community Based Health Insurance member satisfaction and ensuring the program’s long-term sustainability. This comprehensive approach not only improves health outcomes but also strengthens community trust and support for the Community Based Health Insurance initiative.